139k views
4 votes
Simplify 2a²b³(4a² + 3ab² - ab)​

User PeterKA
by
5.3k points

2 Answers

2 votes

Answer:


\large\boxed{8a^4b^3+6a^3b^5-2a^3b^4}

Explanation:


\text{Use the distributive property:}\ a(b+c)=ab+ac\\\\\text{and}\ a^n\cdot a^m=a^(n+m)\\\\2a^2b^3(4a^2+3ab^2-ab)\\\\=(2a^2b^3)(4a^2)+(2a^2b^3)(3ab^2)+(2a^2b^3)(-ab)\\\\=8a^(2+2)b^3+6a^(2+1)b^(3+2)-2a^(2+1)b^(3+1)=8a^4b^3+6a^3b^5-2a^3b^4

User Webpat
by
5.9k points
6 votes

Good evening ,

______

Answer:

8a⁴b³ + 6a³b⁵ - 2a³b⁴

___________________

Explanation:

2a²b³(4a² + 3ab² - ab)​ = 2a²b³×4a² + 2a²b³×3ab² -2a²b³× ab

= 8a⁴b³ + 6a³b⁵ - 2a³b⁴.

:)

User Eirini Graonidou
by
5.2k points